2022
DOI: 10.1021/acs.energyfuels.1c04072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Energy Materials with X-ray Absorption Spectroscopy─Advantages, Challenges, and Opportunities

Abstract: X-ray absorption spectroscopy (XAS) plays a critical role in the characterization of energy materials, including thinfilm electrocatalysts and battery materials. XAS is well-suited for this purpose because it is element-specific and can target distinct chemical environments within a material, even in a mixed or complicated matrix. Even so, some key energy materials are far from "ideal" XAS samples. This means that both sample preparation and experimental conditions need to be considered when collecting and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 101 publications
2
24
0
Order By: Relevance
“…Subsequently, we explore the various NO 3 RR reaction pathways that result in the formation of NH 3 (Figure 3c and Figure S26, Supporting Information). Several steps have been proposed as the RDS on single atoms sites for NO 3 RR, including the first step of NO 3 adsorption, *NO reduction to *NHO, and *NHO reduction to *N. [22,41] However, we find that the reaction pathways exhibit similar energies on each site, which is reflected in our experimental results, where a comparable FE NH4…”
Section: A Higher Fe Nh4supporting
confidence: 41%
See 2 more Smart Citations
“…Subsequently, we explore the various NO 3 RR reaction pathways that result in the formation of NH 3 (Figure 3c and Figure S26, Supporting Information). Several steps have been proposed as the RDS on single atoms sites for NO 3 RR, including the first step of NO 3 adsorption, *NO reduction to *NHO, and *NHO reduction to *N. [22,41] However, we find that the reaction pathways exhibit similar energies on each site, which is reflected in our experimental results, where a comparable FE NH4…”
Section: A Higher Fe Nh4supporting
confidence: 41%
“…Subsequently, we explore the various NO 3 RR reaction pathways that result in the formation of NH 3 (Figure 3c and Figure S26, Supporting Information). Several steps have been proposed as the RDS on single atoms sites for NO 3 RR, including the first step of NO 3 – adsorption, *NO reduction to *NHO, and *NHO reduction to *N. [ 22,41 ] However, we find that the reaction pathways exhibit similar energies on each site, which is reflected in our experimental results, where a comparable FE NH4 + is achieved with each catalyst across the potential range tested. We note that in one modeled pathway (Figure 3c), a significant difference is seen in the energy for *NH formation on the Cu‐N 4 sites (Figure 3c), of −4.43 eV (leading to an uphill process) compared to −7.17 eV and −6.51 eV on Cu‐N 3 ‐C 1 and Cu‐N 2 ‐C 2 sites, respectively.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, the data collected at the Mo K-edge notably differ from the Ni, Co, and Fe K-edge EXAFS for the respective bimetallic materials (Figure b), neither of which exhibited a pronounced second peak in the Fourier transform data (Figure c). This indicates that the dominant location of secondary metals is not within an ordered crystalline environment, i.e., provides more strong evidence against substitutional doping of MoS 2 with nickel, cobalt, and iron sulfides.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the data collected at the Mo Kedge notably differ from the Ni, Co, and Fe K-edge EXAFS for the respective bimetallic materials (Figure 3b), neither of which exhibited a pronounced second peak in the Fourier transform data (Figure 3c). This indicates that the dominant location of secondary metals is not within an ordered crystalline environment, 112 i.e., provides more strong evidence against substitutional doping of MoS 2 with nickel, cobalt, and iron sulfides. Simulations of the EXAFS at the secondary metal K-edges for the MS x /MoS 2 LE materials demonstrated that the data could be reasonably well described with a first coordination sphere of sulfur but not oxygen (Table S1 and Figure S10).…”
Section: Lementioning
confidence: 96%